To analyze the function depicted in the table, we first look at the given pairs of \(x\) and \(f(x)\):
\[ \begin{array}{|c|c|} \hline x & f(x) \ \hline -1 & -7 \ 0 & -48 \ 1 & -171 \ 2 & -376 \ 3 & -663 \ \hline \end{array} \]
Next, let’s examine how \(f(x)\) changes as \(x\) increases. A common approach to determining the type of function is to look at the differences between successive values of \(f(x)\).
-
Calculate the first differences (\(f(x+1) - f(x)\)):
- For \(x = -1\) to \(0\): \(-48 - (-7) = -41\)
- For \(x = 0\) to \(1\): \(-171 - (-48) = -123\)
- For \(x = 1\) to \(2\): \(-376 - (-171) = -205\)
- For \(x = 2\) to \(3\): \(-663 - (-376) = -287\)
First differences: \(-41, -123, -205, -287\)
-
Next, calculate the second differences:
- From \(-41\) to \(-123\): \(-123 - (-41) = -82\)
- From \(-123\) to \(-205\): \(-205 - (-123) = -82\)
- From \(-205\) to \(-287\): \(-287 - (-205) = -82\)
Second differences: \(-82, -82, -82\)
Since the second differences are constant, we can conclude that \(f(x)\) is a quadratic function.
Thus, we can fill in the answer:
This function is a quadratic function because the second differences of \(f(x)\) are constant.